Evolutionary game of life-cycle types in marine benthic invertebrates: Feeding larvae versus nonfeeding larvae versus direct development. (21st March 2022) - Iwasa, Yoh; Yusa, Yoichi; Yamaguchi, Sachi
Highlights: Many marine invertebrates have benthic adults with planktonic feeding larvae. Some species have nonfeeding planktonic larvae which settle and start benthic stages. Still others skip planktonic stages, and adults produce benthic offspring. We developed an evolutionary game to explain the evolution of these life cycles. Productivity of pelagic life and stability of benthic habitat determines evolution. Abstract: Many marine invertebrates have a benthic adult life with planktonic long feeding larval stages (planktotrophy). In other species, planktonic larvae do not eat, and after a rather short period, they settle and initiate their benthic stages (lecithotrophy). Still other species skip planktonic larval stages altogether, and adults produce benthic offspring (direct development). In this paper, we develop an evolutionary game among different life-cycle types and examine the conditions for each life-cycle type to win in a seasonal environment. The growth rate and mortality of benthic individuals are the same among all three life-cycle types, the local habitat (patches) for benthic individuals have a finite longevity, and adults may engage in a limited dispersal just before breeding. Planktotrophy evolves if the planktonic stages are more efficient in terms of biomass gain than benthic life. Otherwise, lecithotrophy or direct development should evolve. Among them, direct development is more advantageous than lecithotrophy if the cost of having planktonic larvae is large, the habitat for benthic individuals is stable, and adults engage in some dispersal.